The Relationship Between Organizational Ethical Climate, Organizational Trust, Perceived Stress, And Work Engagement: Perception Of Public-Sector Employees In The West Bank, Palestine - Jarrar, Tariq T M (2022)
The current study intends to examine the relationships between organizational ethical climate dimensions (instrumental climate, caring climate, independence climate, rules climate and law and codes climate) and mediating role of organizational trust, perceived stress as a moderator and work engagement dimensions (vigor, dedication, and absorption). The current study provides better understandings for the practitioners and academicians on the concept of organizational ethical climate, organizational trust, perceived stress and work engagement in a Palestinian context. Supported by Social Exchange Theory (SET) and Theory of Moral Development (ToMD), this study utilized a research model to examine the dimensions of organizational ethical climate i.e., instrumental climate, caring climate, independence climate, rules climate and law and codes climate and work engagement, with mediating variable of organizational trust, as well as moderating variable of perceived stress. A total of 200 respondents from targeted employees of 21 employees from ministries in the West Bank of Palestine participated in this study, and Partial Least Square – Structural Equation Modeling (PLS-SEM) software is employed to test the research model and analyze the data. The present study intends to examine the organizational ethical climate, organizational trust, perceived stress, and work engagement in Palestinian ministries from the perspective of executive employees. This study proposes and analyzes a research framework that integrates all dimensions of organizational ethical climate, organizational trust, perceived stress and work engagement. For this purpose, The researcher uses 26 hypotheses that showed that organizational ethical climate practices have significant effects on organizational trust, and that organizational trust have significant effects on work engagement, and that perceived stress have significant effects on work engagement.